Diet and Menstrual Disorders in Women of Fertile Age (JURNAL PROTEKSI KESEHATAN, 2025)
Menstrual disorders are caused by diet and sedentary life, stress, disease, genetic. The purpose of the study was to determine the relationship between the frequency of junk food consumption and menstrual cycle disorders. This study used a cross sectional design with respondents involved were WUS visiting the catin clinic at Puskesmas Duren Sawit, East Jakarta. The number of respondents was 55 people. Data analysis using chi square test. The results of the study respondents whose menstrual cycle was not normal as much as 23.6%. The youngest age of menarche was 12 years. The frequency of junk food consumption in the category of frequent consumption (7 times / week) is a group of foods / drinks containing a lot of sugar, fried foods, processed meat foods by 81.8%, 67.3%, 36.4%. The results of the chi square test showed that there was a significant relationship between the frequency of junk food consumption and menstrual cycle disorders with P